Accuracy and determinants of self-assessed euro area house prices - Julien Le Roux; Moreno Roma (European Central Bank (ECB), 2019)
Using microdata from the second wave of the Household Finance and Consumption Survey, we investigate the accuracy of property values estimated by homeowners - so called "self-assessed" house prices - and explore the drivers of possible deviations of these prices from official hedonic house price indices. We find evidence that euro area homeowners overestimate the value of their properties by around 9%. Across the largest euro area countries, the overestimation lies in a range between 3.2% in Germany and 22% in Italy. Household characteristics, including the level of indebtedness, appear to explain significant discrepancies between hedonic and self-assessed house price indices, while the limited available data related to property characteristics are generally not affecting this gap. For the euro area, we find that higher self-assessed house prices are associated with a mild increase in consumption expenditures.
Keywords: E31; C21; O18; 330; house prices; micro data; under/overvaluation; wealth effects; quantile regressions